Manajemen Pembelajaran Berbasis Teknologi Informasi dan Komunikasi di SD Negeri 41 Plus Banyuasin III: Information and Communication Technology-Based Learning Management at SD Negeri 41 Plus Banyuasin III - Lina Susanti; Bukman Lian; Nurlina Nurlina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study describes the planning, implementation, and evaluation of Information and Communication Technology (ICT)-based learning at SD Negeri 41 Plus Banyuasin III. The approach used was descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Key informants included the principal and five teachers who were selected purposively. Data validity was maintained through triangulation of sources and techniques. At the same time, analysis followed the interactive model of Miles & Huberman: data reduction, data presentation, and repeated drawing and verification of conclusions. The results showed that the planning was carried out systematically through needs analysis, ICT integration in teaching tools/RPP, scheduling, and strengthening teacher competencies through training and mentoring. During implementation, ICT was utilised for material reinforcement, task differentiation, and learning collaboration through LMS, video conferencing, and game-based learning platforms, which resulted in increased student interaction, motivation, and independence. Evaluation was conducted periodically through structured reflection, peer assessment, and digital portfolios, accompanied by external collaboration to improve infrastructure and content. Overall, ICT-based learning management was deemed effective in supporting the achievement of learning objectives and strengthening 21st-century skills. Recommendations include strengthening educators' ICT competencies, gradual procurement/maintenance of devices, optimizing connectivity, and ongoing monitoring and evaluation.